Severe jaundice due to coexistence of Dubin-Johnson syndrome and hereditary spherocytosis: A case report - Uğur KORKMAZ; Ali Erkan DUMAN; Deniz ÖĞÜTMEN KOÇ; Yeşim Gürbüz; Gökhan Dindar; Fatih ENSAROĞLU; Selçuk Yusuf ŞENER; Ömer ŞENTÜRK; Sadettin HÜLAGÜ (Turkish Journal of Gastroenterology, 2019)
-